Peluang dan Tantangan Penggunaan Sosial Media dalam Membangun Wacana Berhenti Merokok di Indonesia - Sitohang, Marya Yenita (Jurnal Studi Komunikasi dan Media, 2023)
The use and availability of social media have grown exponentially, providing new opportunities to support smoking cessation efforts. Social media encompasses various interactive platforms, enabling individuals and communities to exchange information within a virtual network. This study aims to identify discourses related to smoking cessation encouragement among Indonesian people in social media. To collect data on social media, particularly Twitter, the researchers used Netlytic as a tool and limited the keyword to "rokok" in the Indonesian language. Content analysis was used to analyse collected tweets and identify themes related to smoking. Social network analysis was also conducted to identify actors and relationship between actors. The study found that discourse around smoking can either support smoking cessation intervention, normalise smoking and cigarettes, which may not support cessation efforts, or be neutral. Themes that support smoking cessation efforts include sharing experiences as a second-hand smoker, discomfort having a smoking partner, family members' sickness due to smoking, and reporting health disadvantages of smoking. Besides, smoking was normalised, and its devastating health effects were neglected since people saw smoking as a "teman ngopi". Smoking cessation campaigns on social media can use relevant threads on Twitter to make them more relatable to encourage smoking cessation.